Investigation of leakage and self-healing of direct tension cracks under sustained loading and high-water pressure. (18th January 2021) - Hooshmand, Ahmad; Kianoush, Reza; Siad, Hocine; Lachemi, Mohammed; Moslemi, Mehdi
Highlights: A test setup was used to simulate the leakage/healing in liquid containing structures. Microstructural studies were completed on top, core and bottom layers of cracks. Leakage under high water pressure confirmed the high advantage of using ECC over NC. ECC has significant healing capability under sustained load and high-water pressure. Self-healing process under high-water pressure was different than normal conditions. Abstract: In this study, the leakage/self-healing of direct tension cracks of Normal Concrete (NC) and Engineered Cementitious Composite (ECC) panels have been investigated under the combined effect of sustained loading and high-water pressure. A test setup was designed and used to simulate the leakage in Liquid Containing Structures (LCS). The panels were subjected to direct tensile force in order to form full depth cracks through thickness. The water leakage test was then performed on the cracked panels and the water leakage through the cracks was studied under sustained loading with different water pressures. The leakage rate was recorded over time to study the short- and long-term self-healing of cracks. Furthermore, microstructural studies were completed on full depth drilled cores obtained from the self-healed sections of ECC and NC panels. The samples used for SEM-EDS analyses were taken from the top, middle and bottom portions of the healed cracks to investigate the potential influence of pressurized water on the self-healing products of different elevations of cracks. The results of this study confirm a greater self-sealing of leakage in loaded ECC panel and reveal a high effect of water pressure on the self-healing ability of concretes. Also, diverse concentrations of calcite and intermixed C-S-H/CH were characterized in various locations of healed cracks. Thus, unlike the normal water environment, the process of self-healing under high water pressure started from the middle portion of cracks and then propagated toward the lower and top parts.